Donor lymphocyte infusion after allogeneic stem cell transplantation. Issue 3 (June 2016) - Castagna, Luca; Sarina, Barbara; Bramanti, Stefania; Perseghin, Paolo; Mariotti, Jacopo; Morabito, Lucio
Abstract: Allogeneic stem cell transplantation (allo-SCT) is considered the cornerstone in the treatment of several malignant and not malignant hematological diseases. However, relapse of hematological disease after allo-SCT is considered the most challenging point in the field. The risk can be reduced through optimal patients, donor and disease selection before allo-SCT, but harnessing donor immune system is an appealing way to treat or avoid disease relapse. Donor lymphocyte infusion (DLI) is a simple and effective therapy after allo-SCT. In this paper, the efficacy of DLI will be analyzed in different hematological diseases, focusing also on their therapeutic or pre-emptive use.